Strategic risk taking : a framework for risk management - Damodaran, Aswath (Upper Saddle River, United States Pearson Education, Inc, 2008)
Groundbreaking book that redefines risk in business as potentially powerful strategically to help increase profits. Get out of your "defensive crouch": learn which risks to avoid, which to mitigate, and which to actively exploit.
Keywords: Risk management